Some Methods of Discovering a Problem Situation in Teaching Students and Resolving the Situation - Rahmonqulovich, Rahmonqulov Rayimqul; Qahramonovich, Toshtemirov Kamol; Ayubjonovna, Toshtemirova Gulnora (Researchparks Publishing, 2023)
This article is dedicated to the audience's opinion on creating a problem situation during the course of the lesson, creating a short program suitable for this topic and finding the correct solution to the problem created using it. When learning in technical sciences, a subject is covered using a downloadable program, as it differs from existing software packages, the order of the lesson is given based on the above-mentioned idea.